0025 Hepatocyte HIF-1 Mediates Gene Expression Changes Affecting Hepatic Fibrosis In Murine NAFLD. (27th April 2018) - Mesarwi, O A; Shin, M; Bevans-Fonti, S; Moya, E; Polotsky, V Y; Xu, G; Fisch, K; Malhotra, A
Abstract: Introduction: Obstructive sleep apnea (OSA) is associated with nonalcoholic fatty liver disease (NAFLD) and liver fibrosis. This association is related to the hypoxic burden of OSA, although mechanisms are unclear. We have shown that hepatocyte HIF-1 promotes liver fibrosis in mice with diet-induced obesity. Since HIF-1 primarily functions as a transcription factor to regulate the cellular response to hypoxia, we hypothesized that hepatocyte knockout of HIF-1 would cause gene expression differences yielding observed phenotypic variations. Methods: Eight-week-old mice with hepatocyte-specific HIF-1α knockout ( Hif1a F/F Alb-Cre +/+ ), and Hif1a F/F Alb-Cre -/ - mice serving as wild-type controls, were all fed a high trans -fat diet for six months to mimic human NAFLD, inducing profound steatohepatitis. Upon sacrifice, livers were assessed for fibrosis by Sirius red staining and hydroxyproline assay. RNA was extracted from liver tissue; highest quality samples were used to generate RNA sequencing libraries. Libraries were sequenced with 50 bp single end reads to a depth of approximately 50 million reads/sample. The edgeR and limma packages were used to direct differential expression analysis. Functional enrichment of the differentially expressed genes was performed using the ToppGene Suite. Results: Knockout mice had a 56% reduction in liver fibrosis as measured by hydroxyproline content (liver collagen in knockout: 2.67 ± 0.40 μg/mg, versus wild-type: 1.17 ± 0.21 μg/mg, p=0.028). Samples had a sufficient number of unique aligned reads (44.0–49.7 million). Based on 12, 530 gene expression comparisons, 17 genes were differentially expressed with statistical significance (p<0.05 adjusted for multiple comparisons). Genes with differential expression at an adjusted significance of p<0.2 (150 individual genes) were included in Toppgene enrichment analysis. "Liver fibrosis, experimental" was the most significantly altered gene expression pathway, with 45 of the 150 genes differentially expressed, of 767 in the described pathway (p<10 –29 ). Conclusion: Hepatocyte HIF-1 mediates liver fibrosis in mice with diet-induced obesity, suggesting a mechanistic role for hypoxia in OSA-induced NAFLD progression. Gene expression changes may explain the observed phenotype. Additional mechanistic studies are needed to identify HIF-1 targets in this paradigm. Support (If Any): This work is supported by a grant from the American Sleep Medicine Foundation.